Services Trade Restrictiveness Index (STRI): Audio-visual Services - Nordås, Hildegunn Kyvik (OECD Trade Policy Papers, 2014)
This paper presents the services trade restrictiveness indices (STRIs) for motion pictures, television and broadcasting and sound recording. The STRIs are composite indices taking values between zero and one, zero representing an open market and one a market completely closed to foreign services providers. The indices are calculated for 40 countries, the 34 OECD members and Brazil, China, India, Indonesia, Russia and South Africa. The STRIs capture de jure restrictions. This report presents the first vintage of indicators for audio-visual services and captures regulations in force in 2013. The scores range between 0.06 and 0.72 for motion pictures, 0.07 to 0.78 for television and broadcasting, and between 0.05 and 0.37 for sound recording. The sample averages are 0.18 for motion pictures, 0.28 for television and broadcasting and 0.16 for sound recording. Limitations on foreign entry, including foreign equity limits contribute to about two thirds of the index values in television and broadcasting. In motion pictures screen quotas contribute to the indices in many of the countries with scores above average. Sound recording, i.e. music, is the most open of the three audio-visual services sectors where limitations on movement of people account for more than 40% of the index value. The paper presents the list of measures included in the indices, the scoring and weighting system for calculating the indices and an analysis of the results